FAKTOR - FAKTOR YANG MEMPENGARUHI NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT - Samsul Arifin; Shany Mayasya (Jurnal Ekonomi-Qu, 2018)
The phenomenon that often occurred in connection with the exchange rate fluctuations in currency values is uncertain. Changes in behavior rupiah exchange rate against the U.S.dollar that occurred in Indonesia are affected by economic fundamentals and openness factors. The aim of this research is to analyze the influence of inflation, interest rate, openness, andexchange rate volatility Rp/USD to the exchange rate of rupiah exchange rate against the U.S. dollar. This research used Autoregressive Conditional Heteroskedasticity (ARCH) and Generalized Autoregressive Conditional Heteroscedasticity (GARCH) method. This research used three monthsdata started at the first three months in 2007 until the fourth three months in 2014.According to the result of partial test results (z test) indicates that inflation, interest rate, openness and exchange rate volatility Rp/USD positive and significant effect on rupiah exchange rate againstthe U.S dollar partially. While the simultaneous test (F test) indicates that inflation, interest rate,openness and exchange rate volatility Rp/USD has significant effect on rupiah exchange rate against the U.S dollar simultaneously.